2004
DOI: 10.1159/000077489
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic damage in lymphocytes for the purpose of dose reconstruction: a review of three recent radiation accidents

Abstract: The analysis of chromosomal aberrations in peripheral blood of radiation accident victims is an established method of biological dosimetry. The dose estimate on the basis of an in vitro calibration curve is straightforward when the radiation exposure is homogeneous and the analysis not delayed. In recent years three radiation accidents occurred, where the irradiation or sampling conditions precluded a simple estimation of the dose. During the Georgian accident soldiers carried in their pockets small sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 10 publications
0
15
1
8
Order By: Relevance
“…In the present study, chromosome aberration analysis demonstrated a critical role in estimating the radiation dose and facilitating an accurate clinical diagnosis. Several previous studies have found that the distribution pattern of dic+r exhibits a Poisson distribution among radiated lymphocytes in subjects uniformly exposed to low linear energy transfer (LET) radiation [6,8], whereas the pattern of dic+r distribution does not follow a Poisson distribution in subjects non-uniformly or locally exposed to LET radiation. Of the three subjects in the present study, C received uniform radiation, whereas A and B both received non-uniform radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, chromosome aberration analysis demonstrated a critical role in estimating the radiation dose and facilitating an accurate clinical diagnosis. Several previous studies have found that the distribution pattern of dic+r exhibits a Poisson distribution among radiated lymphocytes in subjects uniformly exposed to low linear energy transfer (LET) radiation [6,8], whereas the pattern of dic+r distribution does not follow a Poisson distribution in subjects non-uniformly or locally exposed to LET radiation. Of the three subjects in the present study, C received uniform radiation, whereas A and B both received non-uniform radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the chromosome aberration assay has been widely used as a sensitive biomarker for dose reconstruction following radiation exposure [3][4][5][6]. In particular, the analysis of dicentric chromosomes and rings (dic+r), two aberrations exemplifying inter-and intrachromosomal exchanges, respectively, has been generally considered to be the standard means for estimating biodosimetry based on its well-established dose-response relationship with radiation exposure and its low baseline levels in the general population [7,8].…”
mentioning
confidence: 99%
“…Doses based on dicentric observation have already been published in 2004 (Wojcik et al 2004). When the present study is compared with the previous one, some slight differences can be observed in the dicentric dose estimation.…”
Section: Resultsmentioning
confidence: 99%
“…They were the most exposed people and those having the highest number of radiological impacts all over their body (33 patches in the case of EP). The calculated percentage of blood exposed is described in the Wojcik et al (2004) paper. This was 40% for AN and 50% for EP.…”
Section: Resultsmentioning
confidence: 99%
“…지금까지 연구되어진 감마선 노출에 대한 인체의 임상적인 부작용은 노출된 조사선량에 따라서 100~300 Gy에서의 중 추신경 장해, 10~30 Gy의 위장관 장해, 4~8 Gy의 골수 장해, 저선량 장해 (1~2 Gy 이하) 등으로 보고되고 있으며, 각각의 급성, 만성 또는 유전 효과에 대하여 연구가 진행되고 있다 [9]. 그러나 감마선에 대한 유해성 평가에 관한 연구는 대부 분 고선량 방사선을 이용한 방사선 치료 및 부작용에 관한 연구가 주로 이루어졌으며, 저선량 방사선 (1~2 Gy 이하) 또 는 1 Gy 이하의 노출로 인한 인체 영향에 대해서는 연구가 매우 미흡한 실정이다.…”
unclassified